The Use of Marketing Minimalism in Marketing Management Firm - Strejčková, Věra; Hesková, Marie, 1948-; Harantová, Monika; Vysoká škola ekonomická v Praze. Fakulta managementu (2017)
The main aim of the diploma thesis The use of marketing minimalism in company management will determine the percentage of success of the reduction of the advertising costs of the product compared to the product existing with the application of low cost marketing communication, using marketing minimalism. The main objective of the thesis is concentrated on the practical part. The key task will be to analyze the marketing strategy of the existing product, to simplify in the context of marketing minimalism. A marketing strategy proposal will be developed using marketing minimalism in a limited liability company.
Vedoucí práce: Marie Hesková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2017
Obsahuje bibliografii
Rok obhajoby 2017
Keywords: strategický marketing; marketingová komunikace; inovace; management [obor dipl. práce]; diplomové práce; strategic marketing; communication in marketing; innovations; master's theses